ROCK PHYSICS ANALYSIS OF THE LRLC PAY ZONE OF CLASTIC RESERVOIR IN X FIELD - Bt Abu Bakar, Ida Farhanatul Adawiyah (Universiti Teknologi PETRONAS, 2014)
Malay basin is located at the eastern part of the Peninsular Malaysia. The project‟s objective is to do analysis of the low resistivity low contrast (LRLC) pay zone of the clastic reservoir in X area that is located within the Malay basin. LRLC pay zone is the hydrocarbon-productive sand zone that shows low resistivity value and lack of resistivity contrast between sand and the adjacent shale in the deep resistivity log curve. The aim of the project is to study the effect of bioturbation clay of sandstone on the resistivity value using some samples from the Gunong Semanggol and study its application towards oil and gas industry by using the well data from X field. The project was divided into 2 parts; general geological study and rock physics analysis. Deliverables of the project were produced using software and laboratory analysis approached. The rock properties of the core sample were obtained by integrating the elastic properties and the bulk properties analysis such as the measure of P wave velocity, S wave velocity and resistivity. Meanwhile the rock properties for the X area were analysed through the well log data. The result shows that the type of fluid content and the presence of clay within the formation will affect the resistivity value that lead to the formation of LRLC zone. This zone can be differentiated by using the rock physics properties.